Parenting and family adjustment scales (PAFAS): validation of a brief parent-report measure for use with families who have a child with a developmental disability - Mazzucchelli, Trevor; Hodges, J.; Kane, R.; Sofronoff, K.; Sanders, M.; Einfeld, S.; Tonge, B.; Gray, K. (Pergamon Press, 2018)
© 2017 Elsevier Ltd Background Children with a developmental disability are three to four times more likely than their typically developing peers of developing significant emotional and behavioural problems. There is strong evidence to suggest that individual biological and psychological factors interact with family functioning to precipitate and perpetuate these problems. Aims This study examined the psychometric properties of a brief measure, the Parent and Family Adjustment Scales (PAFAS) for use with parents of children with a developmental disability. Methods A sample of 914 parents of children (M = 6.27 years) with a developmental disability participated in the study. Disabilities included Autism Spectrum Disorder and Intellectual Disability Results A confirmatory factor analysis supported a 16-item, four factor model of PAFAS Parenting, and an 11-item, three factor model of PAFAS Family Adjustment. The Parenting Scale measures parental consistency, coercive practices, use of encouragement and the quality of parent-child relationship. The Family Adjustment Scale measures parental emotional adjustment and partner and family support in parenting. Conclusions The current study indicated that the PAFAS demonstrates promise as a brief measure of multiple domains of family functioning important for families who have a child with a developmental disability.